Pelatihanan Dan Pengembangan Wirausaha Kecil, Cermat Mengelola Keuangan Usaha Di Kelurahan Bendan Duwur Semarang - Arini Novandalina; Rokhmad Budiyono (Journal of Community Service and Engagement, 2022)
The family is an institution that plays an important role in a society. The existence of a harmonious and happy family can be one form of an advanced society. A prosperous family in it regardless of economic difficulties where the family can meet all the needs of life, starting from the affairs of the stomach, clothing and boards. Currently, many families are aground and fall apart due to the economic factors that hit. The purpose of this activity is to provide training and entrepreneurship development and management for joint business groups as well as housewives and young women in Bendan Duwur Village, Semarang. Through this activity, they motivated the women of Bendan Duwur Village, Semarang to promote local products to become superior products from the City of Semarang in order to face the ASEAN Economic Community (AEC). Furthermore, there is an increase in partners' motivation to become entrepreneurs and improve the quality of their products. Therefore, the importance of careful entrepreneurship development in managing business finances in the household for the family is to be able to plan every household budget for the family, namely to be able to plan every household budget, record keeping, decision making and long-term planning in the household. where the importance of managing finances to be applied in the family